The cleaning of instruments and syringes - Darmady, E. M. (1965)
The dangers to the handler of syringes used for routine injections were found to be negligible, but known infected syringes and those contaminated with antibiotics should be autoclaved before handling as a high proportion of these carry pathogenic organisms. Mechanical methods of cleaning syringes and instruments are assessed. The use of an artificial soil for testing purposes is described. Using this soil, ultrasonics by themselves are inadequate for cleaning syringes and instruments. Agitation with ultrasonics is essential for syringes, but is insufficient for instruments. Detergents are therefore an essential adjunct to the cleaning process. For syringes Pyroneg proved to be the most satisfactory, particularly if they had been previously siliconized. The best detergent for instruments contaminated with these types of soil was Penesolve 814 at a temperature of 95°C. but the instruments must be adequately rinsed after this treatment. A number of other detergents and cleaning agents are discussed.